Strategi Peningkatan Kesejahteraan dan Pengelolaan Keuangan Kelompok Tani Kelapa Makmur melalui Pendekatan Arisan sebagai Skema Keuangan Alternatif di Desa Lombang - Dessy Novitasari Laras Asih; Very Andrianingsih; Moh Faisol (Abhakte Jurnal Pengabdian Kepada Masyarakat, 2025)
Lombang Village in Sumenep Regency relies heavily on seasonal agriculture, particularly watermelon and coconut production, resulting in unstable farmer incomes due to market fluctuations and climate change. The "Kelapa Makmur" Farmers Group operates an informal savings and loan program, but its conventional management limits its effectiveness for productive activities. Low financial literacy and poor business record-keeping hinder the potential of this initiative. This community service program aims to transform arisan into a productive financial scheme and improve members' financial literacy and business planning skills through a structured, participatory approach. Key activities include problem identification, training module development, financial literacy training, mentorship for productive arisan usage, and evaluation. Expected outcomes include better financial skills among members, optimized arisan funds, a transparent financial recording system, and enhanced economic resilience for farmers, ultimately contributing to community economic empowerment.